Five-County Validation of the Indiana Risk Assessment System – Pretrial Assessment Tool (IRAS-PAT) using a Local Validation Approach. (7th October 2020) - Lowder, Evan M.; Lawson, Spencer G.; Grommon, Eric; Ray, Brad R.
Abstract: Local jurisdictions are increasingly using pretrial risk assessment instruments to assess risk of pretrial misconduct and inform release decisions. We adopted a local validation approach to examine the predictive validity of Indiana Risk Assessment System – Pretrial Assessment Tool (IRAS-PAT) assessments in 3, 739 unique pretrial defendants across five Indiana counties. Jail, court, and pretrial risk assessment records were matched within each jurisdiction to examine pretrial misconduct outcomes (i.e., any arrest, any new arrest, and any failure to appear) during the case processing period. Area Under the Curve (AUC) estimates showed good-to-excellent levels of predictive accuracy for total scores for all outcomes (AUC Range: 0.67-0.72). Multivariable models showed defendants assessed at High (OR Range: 5.42-8.62) and Moderate (OR Range: 2.56-3.08) risk had higher rates of pretrial misconduct relative to those assessed at Low risk. Findings provide strong evidence for the predictive accuracy of IRAS-PAT assessments overall, though some item-level considerations are noted.